A INTERDISCIPLINARIDADE NA EXPERIÊNCIA DE PROFISSIONAIS DE SAÚDE EM CENTRO DE ATENÇÃO PSICOSSOCIAL. - MOREIRA, GLAUBER MENDONÇA (2019)
Historically, the challenges posed by the psychiatric reform for the creation of a non-asylum and psychosocial model of mental health care and the adequacy of it to the premisses of the SUS, directly impact the daily work of mental health professionals. Moreover, the interdisciplinary aspects of the health team emerge as a concern to be addressed. In this context, the objective of this study was to analyze the conception of mental health professionals in the Psychosocial Attention Center (CAPS) about the interdisciplinarity in their models of action, through the analysis that make this concept in their practices in the professional practice. It is a study using a qualitative method, and for that, we used non-participant observations in technical meetings at three different CAPS units in the city of Guarulhos, metropolitan region of São Paulo. From this, three professionals were selected for convenience of the technical meetings, being one of each of the CAPS units participating in the research. These professionals answered semi-structured interviews about their perceptions about interdisciplinarity in their work at CAPS. The results point out that interdisciplinarity has been understood as a theoretical concept, and thus, little articulated with the practice of the professionals involved. It was also possible to perceive a lack of knowledge of health professionals about the possibilities of interdisciplinary action, sometimes approaching other practices, such as multidisciplinarity, or confused with simpler strategies of group formation, such as team. Thus, the differences presented in the discourses between interdisciplinary thinking and doing result from the difficulties of concrete actions of these professionals that would certainly allow a more effective work to the users of mental health services.